2017
DOI: 10.15208/beh.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and financial planning: Implication for financial well-being of retirees

Abstract: This study examines how financial literacy, financial behaviour, family support (as another source of income), number of dependents, and retirement planning influence on the financial well-being of retirees in Cape Coast Metropolis of Ghana. A cross-sectional survey strategy was employed on 400 respondents randomly selected from 1500 members of the association to analyze the effect of financial literacy, financial behaviour, family support, number of dependents and retirement planning on financial wellbeing. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 27 publications
6
67
1
3
Order By: Relevance
“…These results are supported by the results of research by Prihartono & Asandimitra (2018), Herawati, Candiasa, Yadnyana, & Suharsono (2018), Kautsar & Asandimitra (2018), Sari (2015), and Akben-selcuk (2015). Otherwise, a study by (Adam, Frimpong, & Boadu, 2017) implied that financial literacy does not affect financial management behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These results are supported by the results of research by Prihartono & Asandimitra (2018), Herawati, Candiasa, Yadnyana, & Suharsono (2018), Kautsar & Asandimitra (2018), Sari (2015), and Akben-selcuk (2015). Otherwise, a study by (Adam, Frimpong, & Boadu, 2017) implied that financial literacy does not affect financial management behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in setting realistic financial targets, commitment to setting targets, and the taking of prompt and appropriate corrective measures are positive consequences of good financial behavior that have the potential to enhance the financial well-being of SME owners in Ghana. This result sits well with that of Adam et al (2017). Thus, the result posits that a one-unit increase in financial behavior could lead to a .32 increase in financial well-being.…”
Section: Discussion Of Regression Resultsmentioning
confidence: 99%
“…Brown, Grigsby, van der Klaauw, Wen, and Zafar () concluded, from a study of the relationship between financial education and debt behavior of the young, that both math and financial literacy education lead to improvement in youth creditworthiness and reduction in the likelihood of the youth carrying debt as well as their average debt balances. Adam et al () assessed whether the financial well‐being of retirees is explained by financial literacy and financial planning. They concluded that financial literacy, retirement planning, and family support significantly impact the financial well‐being of retirees.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent survey of 400 retirees in Cape Coast, Ghana, Adam, Frimpong, and Boadu (2017) examined the financial wellbeing of retirees, and found that financial wellbeing in retirement is affected by financial literacy, retirement planning, and family support. To maximize financial wellbeing in retirement, they recommend among other things that policies should be directed at pre-retirement education and sensitization.…”
Section: The Elderly and Financial Wellbeingmentioning
confidence: 99%